Ultraviolet Photooxidation of Smectite‐Bound Fe(II) and Implications for the Origin of Martian Nontronites. Issue 5 (10th May 2022) - Rivera Banuchi, V. B.; Liu, W.; Yee, N.; Legett, C.; Glotch, T. D.; Chemtob, S. M.
Abstract: Clay minerals detected with orbital and in situ instruments in ancient Martian terrains constrain Mars' climate and aqueous alteration history. Early in its history, Mars experienced an atmospheric redox change and iron‐bearing clay minerals may preserve the effects of that transition. Ferrous smectites, the thermodynamically predicted product of chemical weathering of basalts under anoxic conditions, may have undergone oxidation by exposure to chemical oxidants in the atmosphere or regolith, or by direct photooxidation at the surface. To assess these potential oxidation pathways, ferrous trioctahedral smectites of varying initial iron content were synthesized and subjected to oxidation by ultraviolet (UV) irradiation. Experimental UV irradiation under an anoxic atmosphere equivalent to approximately 7 years of flux on the Martian surface caused partial oxidation of smectite‐bound Fe (Fe 3+ /ΣFe = 16–18%) and octahedral sheet contraction. Metal‐OH vibrational bands in visible/near infrared (VNIR) reflectance spectra of oxidized smectites changed in band depth and asymmetry with higher iron content. X‐ray diffraction patterns of UV irradiated samples indicate the formation of a mixed di‐ and trioctahedral smectite or a secondary nontronite phase, possibly on the surfaces of higher iron content smectites. These experiments suggest that UV irradiation is able to oxidize structurally bound iron in smectites without the presence of other chemical oxidants. Photooxidation may have influenced the mineralogy, both syndepositionally and postdepositionally, of Martian alteration assemblages formed near the surface and this process needs not be limited to one part of their formation history. Plain Language Summary: Martian mineral assemblages observed with orbiters and rover instruments allow us to understand the planet's past climate and aqueous activity. Hydrated minerals that contain Fe(II) are of particular interest as they would have been affected by the early atmosphere becoming more oxidizing overtime, changing the structural iron into Fe(III). In this study, we synthesized Fe(II) smectites with varying iron content and irradiated them with an ultraviolet (UV) light source to test whether they could be photooxidized. Iron in the smectite minerals was incompletely oxidized by UV radiation after being exposed for the equivalent of approximately 7 years of exposure on the early Mars surface. The smectites with higher iron content showed more changes with photooxidation in their visible/near infrared spectra as well as in their X‐ray diffraction patterns, two datasets collected by instruments on currently active Martian missions. These results suggest that UV photooxidation is a plausible contributor to the mineralogy and redox state of clay mineral assemblages observed at the Martian surface. Key Points: Ultraviolet (UV) irradiation of initially ferrous smectites of varying iron content partially oxidized structural iron (Fe 3+ /ΣFe = 16–18%) Smectites with greater iron had more observable changes in their visible/near infrared spectra regardless of the similar extent of oxidation UV photooxidation is proposed as a viable oxidation pathway for surficial Martian smectites